Right-wing extremism in Australia: the rise of the new radical right. Issue 2 (2nd July 2016) - Dean, Geoff; Bell, Peter; Vakhitova, Zarina
ABSTRACT: This research examines the shifting momentum of right-wing extremism (RWE) in Australia. The study provides an in-depth assessment of eight of the most active RWE groups in Australia, through their online presence where they espouse their ideological narrative and propaganda statements. The phenomenon of new radical right (NRR) groups is explored through a three-pronged mixed method research design: Firstly, a content analysis of core narrative themes contained on websites of RWE groups; secondly, a thematic analysis of RWE 'online' discussion forums; and thirdly, a critical analysis of Google Trends data on the shifting patterns of popularity of various extremism-related search terms amongst the general population. A problem–solution mapping tool that was developed for this research that quantifies the 'ideological space' occupied by different 'new' RR groups compared with 'old' RWE groups is presented. The overall findings are that NRR groups pose political and community challenges to the nature of Australian Society. Moreover, there is evidence of a contest for ideological dominance between 'old-style' RWE groups and 'new-style' Radical (Far) Right Extremism groups in Australia. The 'online' forum data and Google trends data confirm this finding. The practical implications of these challenges and the future directions of this research as well as its limitations are discussed.